1998
DOI: 10.1016/s0277-9536(98)00117-8
|View full text |Cite
|
Sign up to set email alerts
|

Well-being of haemophilia patients: a model for direct and indirect effects of medical parameters on the physical and psychosocial functioning

Abstract: Abstract-This study outlines the development and evaluation of a structural equation model for establishing the consequences of haemophilia. The hereditary disorder is characterized by a high tendency to haemorrhages, with recurrent bleeding mto the joints causing irreversible joint damage. The model is, in general, an attempt to answer the following questions: what is the effect of haemophilia on the wellbeing (i.e. satisfaction, health, somatic complaints and self-esteem) of patients and what is the addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
5
33
0
2
Order By: Relevance
“…Optimists tend to have a faster rate of recovery from surgery nature? The effects of medical antecedents on subsequent QoL among optimists may be mediated by more positive appraisals of treatment related side-effects and the use of more positive coping strategies [4,[13][14][15]. However, unrealistic optimism can lead to greater coping difficulties arising from disappointment and probable failure to adequately prepare for likely outcomes [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimists tend to have a faster rate of recovery from surgery nature? The effects of medical antecedents on subsequent QoL among optimists may be mediated by more positive appraisals of treatment related side-effects and the use of more positive coping strategies [4,[13][14][15]. However, unrealistic optimism can lead to greater coping difficulties arising from disappointment and probable failure to adequately prepare for likely outcomes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial variables including optimism partly mediated the effect of disability on global life satisfaction among 980 haemophiliacs [15], while in nasopharyngeal cancer patients, optimism mediates between eating ability and QoL [17]. However, in a cross-sectional study examining the mediating effects of psychosocial variables (including optimism) between disease severity in chronic obstructive pulmonary disease and QoL, optimism did not significantly predict nor mediate QoL [14].…”
Section: Introductionmentioning
confidence: 99%
“…Triemstra et al [26] reported that the effects of joint damage and concomitant disability, more common in patients with severe hemophilia, influence satisfaction with life, health and self-esteem. The anxiety and self-esteem were psychological characteristics with significant differences between the clinical categorization of hemophilia observed.…”
Section: Discussionmentioning
confidence: 99%
“…However people with haemophilia in general may have problems with social participation due to time in hospital and physical inability to participate or attend events/functions (Triemstra et al, 1998); wanting to hide their condition due to discrimination and stigma (Barlow, Stapley, Ellard, & Gilchrist, 2007); or mental health barriers such as stress, high anxiety, low self-esteem, and depression (Ghanizadeh & Baligh-Jahromi, 2009). Considering that Bos (2007) found social support can buffer the ill-effects of illness and stress for older people with haemophilia, strategies are needed to help older people with haemophilia overcome barriers to social participation.…”
Section: Important Social Supports and Services For Older People Withmentioning
confidence: 99%